2012
DOI: 10.3109/1061186x.2012.725405
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of carnosic acid nanoparticulate system for upregulation of neurotrophins in the brain upon intranasal administration

Abstract: To develop formulations of carnosic acid nanoparticles and to assess their in vivo efficacy to enhance the expression of neurotrophins in rat model. Carnosic acid loaded chitosan nanoparticles were prepared by ionotropic gelation technique using central composite design. Response surface methodology was used to assess the effect of three factors namely chitosan concentration (0.1–1% w/v), tri-poly phosphate concentration (0.1–1% w/v) and sonication time (2–10 min) on the response variables such as particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The aniamls were injected with 10 mg/kg or 20 mg/kg carnosic acid nanoparticles for five days. The carnosic acid nanoparticles were prepared according to previous study [10]. Briefly, carnosic acid nanoparticles were developed by ionotropic gelation technique using response surface Histopathological changes of liver tissue samples with H&E staining.…”
Section: Animalsmentioning
confidence: 99%
“…The aniamls were injected with 10 mg/kg or 20 mg/kg carnosic acid nanoparticles for five days. The carnosic acid nanoparticles were prepared according to previous study [10]. Briefly, carnosic acid nanoparticles were developed by ionotropic gelation technique using response surface Histopathological changes of liver tissue samples with H&E staining.…”
Section: Animalsmentioning
confidence: 99%
“…The CA nanoparticles were prepared according to a previous study. 24 Briefly, CA nanoparticles were developed by ionotropic gelation technique …”
Section: Materials and Methods Animals And Ca Preparationmentioning
confidence: 99%
“…21,22 In addition, a study has found that nanoparticulate drug delivery system for CA intranasal administration needed less amounts of administrations to induce the required pharmacological reaction due to its ability to locate on the olfactory mucosal region and supply controlled CA delivery for prolonged time periods. 23,24 Generally, for the potential antiinflammatory and pro-apoptosis of CA in cancer cells and easier absorbance of nanoparticles, CA nanoparticles could be used as a candidate, which is likely to improve anticancer effects. And the focus will be on evaluating the effect of CA nanoparticles on liver cancer cells in vitro and in vivo experiments through regulating inflammation response and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Use of vasoconstrictors to reduce the clearance in to the blood and treatment with inhibitors of the efflux transporters reduces the clearance in to the blood and enhances the drug to the CNS. Vaka et al investigated the capabilities of carnosic acid nanaoparticular systems to enhance the in vivo efficacy of carnosic acid and enhance the neurotropin expression in the brain [48][49][50]. It was reported that intranasal administration of carnosic acid nanoparticles resulted in comparable levels of endogenous neurotrophins level in the brain that was equivalent to the four, once a day intranasal administration of solution in rats and demonstrated the fact that nanoparticulate drug delivery system for intranasal administration of carnosic acid reduces the number of administrations to elicit the required pharmacological activity.…”
Section: Nanoparticular Delivery Systemmentioning
confidence: 99%